Military Reform and Militarism in Russia - Golts, Aleksandr (Lynne Rienner Publishers, 2018)
Aleksandr Golts traces the evolution of the Russian military, from the collapse of the Soviet Union to the incursions in eastern Ukraine in 2014-2017. Golts also sheds light on the reemergence of militarism in the Putin era, exploring its origins and making sense of the acceptance of the phenomenon by so much of Russian society.
Keywords: Militarism -- Russia (Federation) -- History.; Russia (Federation) -- Armed Forces -- Reorganization.; POLITICAL SCIENCE / World / Russian & Former Soviet Union.; Vladimir Putin, security.